Integration of Economic and Social Values in Grant Syari’ah - BS, Iman Asroa (Journal of Multidisciplinary Science: MIKAILALSYS, 2023)
This study examines the integration of grant fiqh economic and social values. The problem is that so far, grant studies have tended to be carried out from a fiqh perspective, even though grants have provided many benefits for human life. As a teaching sourced from the Qur'an and Hadith, of course, grants have their own values. From these problems the question arises: How do the Qur'an and Hadith explain the economic and social values of Islamic grants? This research is a library research using a qualitative approach. Data collection is done by examining the content of the arguments about grants contained in the Qur'an and Hadith. The data is processed descriptively which is then presented to answer research problems. The results of the study indicate that there is an integration between grants with economic values and social values in the Qur'an and Hadith. This is evidenced by the existence of the economic and social values of the grants contained in the Qur'an and Hadith in an integrated manner.